2021
DOI: 10.3389/fpls.2021.779970
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Genetic Components Responsible for the Unique Photosynthetic Stem Capability of the Wild Almond Prunus arabica (Olivier) Meikle

Abstract: Almond [Prunus dulcis (Mill.) D. A. Webb] is a major deciduous fruit tree crop worldwide. During dormancy, under warmer temperatures and inadequate chilling hours, the plant metabolic activity increases and may lead to carbohydrate deficiency. Prunus arabica (Olivier) Meikle is a bushy wild almond species known for its green, unbarked stem, which stays green even during the dormancy period. Our study revealed that P. arabica green stems assimilate significantly high rates of CO2 during the winter as compared t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…This similarity raised the assumption that P. arabica green stems have a photosynthetic capability (Sorkheh et al, 2009). Indeed, in a recent detailed genetic and physiological study, we have provided for the first time experimental evidence supporting P. arabica stem photosynthesis capability [SPC, (Brukental et al, 2021)]. Our study showed that P. arabica green stems are photosynthetically active all year round, including during the winter months after the tree sheds its leaves and enters its dormancy period.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…This similarity raised the assumption that P. arabica green stems have a photosynthetic capability (Sorkheh et al, 2009). Indeed, in a recent detailed genetic and physiological study, we have provided for the first time experimental evidence supporting P. arabica stem photosynthesis capability [SPC, (Brukental et al, 2021)]. Our study showed that P. arabica green stems are photosynthetically active all year round, including during the winter months after the tree sheds its leaves and enters its dormancy period.…”
Section: Introductionsupporting
confidence: 54%
“…With no photosynthetic organs (leaves) during dormancy, to regain carbon loss, these conditions challenge the almond tree's carbon reserves, and, eventually, its productivity (Zwieniecki and Secchi, 2015;Sperling et al, 2019). Photosynthetic stems, which have never been described before in deciduous fruit crop trees (until our work by Brukental et al, 2021), can thus contribute to the net carbon gain, and increase the tree resilience to extreme environmental conditions.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations